The Combined Effects of Increased pCO2 and Warming on a Coastal Phytoplankton Assemblage: From Species Composition to Sinking Rate - Feng, Yuanyuan; Chai, Fei; Wells, Mark L.; Liao, Yan; Li, Pengfei; Cai, Ting; Zhao, Ting; Fu, Feixue; Hutchins, David A. (Frontiers in Marine Science, 2021)
In addition to ocean acidification, a significant recent warming trend in Chinese coastal waters has received much attention. However, studies of the combined effects of warming and acidification on natural coastal phytoplankton assemblages here are scarce. We conducted a continuous incubation experiment with a natural spring phytoplankton assemblage collected from the Bohai Sea near Tianjin. Experimental treatments used a full factorial combination of temperature (7 and 11°C) and pCO2 (400 and 800 ppm) treatments. Results suggest that changes in pCO2 and temperature had both individual and interactive effects on phytoplankton species composition and elemental stoichiometry. Warming mainly favored the accumulation of picoplankton and dinoflagellate biomass. Increased pCO2 significantly increased particulate organic carbon to particulate organic phosphorus (C:P) and particulate organic carbon to biogenic silica (C:BSi) ratios, and decreased total diatom abundance; in the meanwhile, higher pCO2 significantly increased the ratio of centric to pennate diatom abundance. Warming and increased pCO2 both greatly decreased the proportion of diatoms to dinoflagellates. The highest chlorophyll a biomass was observed in the high pCO2, high temperature phytoplankton assemblage, which also had the slowest sinking rate of all treatments. Overall, there were significant interactive effects of increased pCO2 and warming on dinoflagellate abundance, pennate diatom abundance, diatom vs. dinoflagellates ratio and the centric vs. pennate ratio. These findings suggest that future ocean acidification and warming trends may individually and cumulatively affect coastal biogeochemistry and carbon fluxes through shifts in phytoplankton species composition and sinking rates.